2023
DOI: 10.1037/xap0000412
|View full text |Cite
|
Sign up to set email alerts
|

Easily accessible but easily forgettable: How ease of access to information online affects cognitive miserliness.

Abstract: Ubiquitous Internet access has provided easy access to information and has influenced users' attention and knowledge management. In an online information service context, this research examines how the perception of easy access to information affects strategies to learn two types of information: "what it is" and "how to access it." This study also examines how the learning process is moderated by individual differences in working memory capacity, which can determine efficient management of attentional resource… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…The cognitive psychology literature makes several key theoretical and modeling predictions regarding learning through spaced retrieval practice. First, the rate of forgetting is not constant, but varies by student (Kang, 2023;Unsworth, 2019;Walsh et al, 2018), content (Tozios & Fukuda, 2020), and the sequence of learning and testing itself (Vlach & Kalish, 2014).…”
Section: Spaced Retrieval Practice and Forgettingmentioning
confidence: 99%
“…The cognitive psychology literature makes several key theoretical and modeling predictions regarding learning through spaced retrieval practice. First, the rate of forgetting is not constant, but varies by student (Kang, 2023;Unsworth, 2019;Walsh et al, 2018), content (Tozios & Fukuda, 2020), and the sequence of learning and testing itself (Vlach & Kalish, 2014).…”
Section: Spaced Retrieval Practice and Forgettingmentioning
confidence: 99%
“…In other words, cognitive misery is caused by the availability of online information and the efficient use of attentional resources, not by users' lack of cognitive ability. (Kang, 2022) This is because people, particularly those with a high working memory capacity, are less likely to remember details but more likely to remember how to access information (a keyword for a search engine query). (Hamzi et al, 2021) But people who are not confident in their ability to remember tend to use external tools (Fisher & Oppenheimer, 2021) making the 2011 statement (Sparrow et al, 2011) increasingly valid.…”
Section: Effects Of Digital Tools On Memorization and Learningmentioning
confidence: 99%
“…We conclude that, under certain conditions, the use of digital tools can be harmful by impairing cognitive functions such as memorization. (Kang, 2022) Given the limited number of studies that have examined the effects of flipped classrooms on the memorization of college students, especially in subjects such as life and earth sciences, the purpose of this study will be to examine this avenue by questioning the usefulness of digital tools in such a pedagogical approach based on the following hypothesis. paper-based resources cannot replace digital tools in the flipped classroom approach, as their impact on memory retention during learning may be less significant compared to digital tools.…”
Section: Effects Of Digital Tools On Memorization and Learningmentioning
confidence: 99%
“…In the study conducted by Kang (2023), participants were shown a credit card advertisement highlighting its benefits in bullet points. One group (the easy access condition) was told they could use a specific keyword to search for the credit card later.…”
Section: The Google Effect: a Case Of Directed Forgetting?mentioning
confidence: 99%
“…Furthermore, people distinguish between searchable and non-searchable information and exhibit worse memory for the former (Macias et al, 2015). Also, when information is readily accessible, people tend to remember the retrieval method rather than the content itself (Kang, 2023) Finally, people seem to be prone to incorrectly assessing the memorability of a piece of information based on how quickly it can be retrieved (Storm & Stone, 2021).…”
Section: The Google Effect: a Case Of Directed Forgetting?mentioning
confidence: 99%